Morphology and thermal properties of polypropylene-montmorillonite nanocomposite using modified bentonite of Bener Meriah Aceh - JULINAWATI JULINAWATI; BASUKI WIRJOSENTONO; EDDIYANTO EDDIYANTO; SAHARMAN GEA; ICHWANA RAMLI (Jurnal Natural, 2020)
Research on the use of modified bentonite from Bener Meriah Aceh to study the morphology and thermal properties of polypropylene-montmorillonite nanocomposite (PP-MMT) was carried out. Bentonite was isolated into nano-sized montmorillonite and modified with the addition of PP-g-MA as a compatibilizer and octadecylamine as a modifier of MMT. PP-MMT nanocomposite processing was carried out in an internal mixer at 180 oC with a time of 10 minutes, and a speed of 65 rpm. Based on the results of the TGA-DTA test, the modified bentonite from Bener Meriah Aceh with PP-g-MA and octadecylamine can improve the thermal properties of PP-MMT nanocomposite in a composition comparison of  PP; PP-g-MA; MMT is 85; 10; 5. The SEM test results also showed that exfoliation and intercalation had occurred of MMT at PP-MMT nanocomposite.